THE EFFECT OF HYPNOPARENTING AS AN EFFORT TO IMPROVE THE APPETITE OF PRESCHOOL-AGED CHILDREN WITH PICKY EATER - Hafiza, Merizka; Ariani; Rahayu, Indriati Dwi (Universitas Brawijaya, 2023)
Picky eater is a child eating problem that is often complained of by parents which causes a low appetite at mealtimes, usually occurring in preschool-aged 3-5 years. Picky eaters accompanied by a decrease in appetite if left unchecked for a long time can cause children to lack nutritional intake which results in a low nutritional status of children. Parents' efforts are needed to fix children's eating problems, which is hypnoparenting. Hypnoparenting is applied as coaching children with the principle of hypnosis through suggestions given by parents to the child's subconscious mind. To determine the effect of hypnoparenting as an effort to improve the appetite of preschoolers with picky eaters. The research design uses pre-experimental with one group pretest posttest. The research respondents were 26 children aged 3-5 years. Data collection was carried out by filling out questionnaires (Child Eating Behavior Questionnaire and picky eater questionnaires) which were analyzed using the Wilcoxon test. Obtained from the results of the Wilcoxon analysis test, the significance value of appetite was p value 0.005 ≤ 0.05 and the picky eater's significance value was p value 0.000 ≤ 0.05, then Ha was accepted and H0 was rejected which means there is an influence of hypnoparenting as an effort to improve the appetite of preschool-aged children with picky eaters. 26 preschool-aged children (100%) have poor appetites with picky eaters before hypnoparenting, and 19 preschool-aged children (73.1%) have good appetites without being picky eaters so there are an influence on the appetite of preschool-aged children before and after hypnoparenting.